Disparity Refinement Process Based On Ransac Plane Fitting For Machine Vision Applications - Hamzah, Rostam Affendi; Kadmin, Ahmad Fauzan; Abd Gani, Shamsul Fakhar; Hamid, Mohd Saad; Salam, Saifullah (J Fundam Appl Sci., 2017)
This paper presents a new disparity map refinement process for stereo matching algorithm and the refinement stage that will be implemented by partitioning the place or mask image and re-projected to the preliminary disparity images. This process is to refine the noise and sparse of initial disparity map from weakly textured. The plane fitting algorithm is using Random Sample Consensus. Two well-known stereo matching algorithms have been tested on this framework with different filtering techniques applied at disparity refinement stage. The framework is evaluated on three Middlebury datasets. The experimental results show that the proposed framework produces better-quality and more accurate than normal flow state-of-the-art stereo matching algorithms. The performance evaluations are based on standard image quality metrics i.e. structural similarity index measure, peak signal-to-noise ratio and mean square error.